2002
DOI: 10.1074/jbc.c200296200
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Nervous System-specific Carbohydrate Epitope HNK-1 Exhibit Impaired Synaptic Plasticity and Spatial Learning

Abstract: The HNK-1 carbohydrate epitope, a sulfated glucuronic acid at the non-reducing terminus of glycans, is expressed characteristically on a series of cell adhesion molecules and is synthesized through a key enzyme, glucuronyltransferase (GlcAT-P). We generated mice with a targeted deletion of the GlcAT-P gene. The GlcAT-P ؊/؊ mice exhibited normal development of gross anatomical features, but the adult mutant mice exhibited reduced long term potentiation at the Schaffer collateral-CA1 synapses and a defect in spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(119 citation statements)
references
References 29 publications
(31 reference statements)
4
115
0
Order By: Relevance
“…The smallest critical region (6.8 Mb) that they found extended from D11S1351 (127.5 Mb) to the telomere, and this region was associated with MR. 3 B3GAT1 is expressed in the brain, and this gene is located in the 11q25 at 133.77 Mb. Yamamoto et al 17 reported that when this gene was knocked out, the mice showed impaired synaptic plasticity and learning disorders. Coldren et al have reported two critical regions containing candidate genes for global and selective deficits in neurocognitive function 'BSX for global cognitive function and Neurogranin, a gene essential for synapse plasticity and long-term potentiation, for auditory attention' .…”
Section: Developmental Delaymentioning
confidence: 99%
“…The smallest critical region (6.8 Mb) that they found extended from D11S1351 (127.5 Mb) to the telomere, and this region was associated with MR. 3 B3GAT1 is expressed in the brain, and this gene is located in the 11q25 at 133.77 Mb. Yamamoto et al 17 reported that when this gene was knocked out, the mice showed impaired synaptic plasticity and learning disorders. Coldren et al have reported two critical regions containing candidate genes for global and selective deficits in neurocognitive function 'BSX for global cognitive function and Neurogranin, a gene essential for synapse plasticity and long-term potentiation, for auditory attention' .…”
Section: Developmental Delaymentioning
confidence: 99%
“…Polylactosamine is often modified to carry important carbohydrate structures such as Lewis-related antigens [12][13][14][15], HNK-1 antigen [16], etc., and has many major roles in physiological functions.…”
Section: Introductionmentioning
confidence: 99%
“…HNK-1 carbohydrate has an important role in synaptic plasticity and spine morphogenesis in the nervous system (14,15). These functions are based on its specific expression on certain carriers such as NCAM and GluR2, which is a subunit of the ␣-amino-3-hydroxy-5-methylisoxazole propionate-type glutamate receptor.…”
Section: Discussionmentioning
confidence: 99%
“…HNK-1 carbohydrate has a unique structure, including a sulfated trisaccharide (HSO 3 -3GlcA␤1-3Gal␤1-4GlcNAc-) (9,10), and is biosynthesized by the successive actions of ␤-1,4-galactosyltransferase (␤4GalT), a glucuronyltransferase (GlcAT-P or GlcAT-S), and a sulfotransferase (HNK-1ST) (11)(12)(13). We previously generated mice lacking the gene for GlcAT-P, a major glucuronyltransferase in the nervous system (14). The GlcAT-P-deficient mice showed an almost complete loss of HNK-1 expression in the brain and exhibited reduced long term potentiation at hippocampal CA1 synapses along with impaired maturation of dendritic spines, indicating an important role for this glycan in synaptic plasticity (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation